Karakteristik Klinis pada Pasien Kanker Kolorektal yang Menjalani Kolonoskopi di RSUD Sanjiwani Gianyar Tahun 2019-2020 - I Wayan Budhi Sanjaya; Asri Lestarini; Made Dwi Yoga Bharata (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Colorectal cancer is cancer resulting from cumulative genetic mutations in the epithelial cells of the colon and rectum, resulting in excessive cell division, migration and differentiation and resulting in proliferation, invasion and metastasis of these cells. In 2020, the estimated incidence rate of colorectal cancer in the world will reach 19.5%. In Indonesia, the incidence of colorectal cancer in 2020 reached 34,189 (8.6%) cases. There is no research on the characteristics of colorectal cancer patients at the Sanjiwani Hospital, Gianyar. This study aims to determine the clinical characteristics of colorectal cancer patients who underwent colonoscopy at the Sanjiwani Hospital, Gianyar in 2020. This study uses a cross-sectional descriptive approach, to provide an overview of the characteristics of colorectal cancer patients undergoing colonoscopy at the Sanjiwani Hospital, Gianyar. The samples used were all patients diagnosed with colorectal cancer at the Sanjiwani Hospital, Gianyar for the period January 2019 to December 2020. The results of this study found that the prevalence of colorectal cancer undergoing colonoscopy at the Sanjiwani Hospital, Gianyar in 2019-2020 was 9.5%. The age group is more in the age group of more than 50 years, which is 72.4%. The majority of the research subjects were male with a percentage of 52.6%. 96.1% of the research subjects had no family history. Symptoms of bloody bowel movements were the most common complaints obtained by 22.4%. Adenocarcinoma was the most histopathological picture found, which was 47.4%. The majority of research subjects did not experience anemia by 64.5%. The rectum is the most common location of cancer found that is 72.4%. Stage III is the most common stage found, which is 44.7%. Keywords: Clinical characteristics, colorectal cancer, colonoscopy, Sanjiwani Hospital